Activation of mGluR2/3 underlies the effects of N-acetylcystein on amygdala-associated autism-like phenotypes in a valproate-induced rat model of autism - Chen, Yu-Wen; Lin, Hui-Ching; Ng, Ming-Chong; Hsiao, Ya-Hsin; Wang, Chao-Chuan; Gean, Po-Wu; Chen, Po See (Frontiers in Behavioral Neuroscience, 2014)
Autism-like phenotypes in male valproate (VPA)-exposed offspring have been linked to high glutamatergic neurotransmission in the thalamic-amygdala pathway. Glial cystine/glutamate exchange (system Xc-), which exchanges extracellular cystine for intracellular glutamate, plays a significant role in the maintenance of extracellular glutamate. N-acetylcysteine (NAC) is a cystine prodrug that restores extracellular glutamate by stimulating system Xc-. In this study, we examined the effects of NAC on autism-like phenotypes and neurotransmission in the thalamic–amygdala synapses, as well as the involvement of metabotropic glutamate receptors 2/3 (mGluR2/3). Valproate-treated rats received a single intraperitoneal injection of 500 mg/kg NaVPA on E12.5. On postnatal day 21 (P21), NAC or saline was administered once daily for 10 days. From day 8 to 10, NAC was given 1/2 hour prior to behavioral testing. Chronic administration of NAC restored the duration and frequency of social interaction and ameliorated anxiety-like behaviors in VPA-exposed offspring. In amygdala slices, NAC treatment normalized the increased frequency of mEPSCs and decreased the paired pulse facilitation (PPF) induced by VPA exposure. The effects of NAC on social interaction and anxiety-like behavior in the VPA-exposed offspring were blocked after intra-amygdala infusion of mGluR2/3 antagonist LY341495. The expressions of mGluR2/3 protein and mGluR2 mRNA were significantly lower in the VPA-exposed offspring. In contrast, the mGluR3 mRNA level did not differ between the saline- and VPA-exposed offspring. These results provide the first evidence that the disruption of social interaction and enhanced presynaptic excitatory transmission in VPA-exposed offspring could be rescued by NAC, which depends on the activation of mGluR2/3.